Pulmonary coinfection by Pneumocystis jiroveci and Cryptococcus neoformans - Javier, Bava (Asian Pacific Tropical Medicine Press, 2012)
We communicate the diagnosis by microscopy of a pulmonary coinfection produced by Cryptococcus neoformans and Pneumocystis jiroveci, from a respiratory secretion obtained by bronchoalveolar lavage of an AIDS patient. Our review of literature identified this coinfection as unusual presentation. Opportunistic infections associated with HIV infection are increasingly recognized. It may occur at an early stage of HIV-infection. Whereas concurrent opportunistic infections may occur, coexisting Pneumocystis jiroveci pneumonia (PCP) and disseminated cryptococcosis with cryptococcal pneumonia is uncommon. The lungs of individuals infected with HIV are often affected by opportunistic infections and tumours and over two-thirds of patients have at least one respiratory episode during the course of their disease. Pneumonia is the leading HIV-associated infection. We present the case of a man who presented dual Pneumocystis jiroveci and cryptococcal pneumonia in a patient with HIV. Definitive diagnosis of PCP and Cryptococcus requires demonstration of these organisms in pulmonary tissues or fluid. In patients with < 200/microliter CD4-lymphocytes, a bronchoalveolar lavage should be performed. This patient was successfully treated with amphotericin B and trimethoprim sulfamethoxazole. After 1 week the patient showed clinical and radiologic improvement and was discharged 3 weeks later.